The Impact of Conscious Leadership in Supporting the Requirements of Strategic Renewal: An Analytical Study in the Iraqi Ministry of Planning - Mahmood Khalil * , Maryam; Abdul Qadir AL- Nuaimi, Salah (Journal of Economics and Administrative Sciences, 2024)
The current research aims to explore the relationship and impact of conscious leadership, (self-awareness, awareness of others, and situational awareness), on strategic renewal, (context, content, process). The research problem relies on the following question: Do the responsible leaders in the Ministry of Planning possess a level of awareness to meet the requirements of strategic renewal for the present and the future? The research community consists of top and middle leaders in the Ministry of Planning, totaling 100 out of 104. Data analysis was conducted using statistical software, including SPSS v.26, Amoss v.29, and Picelscp Professor. Among the key findings, it is stressed that there is a need to enhance the importance of self-awareness, awareness of others, and situational awareness. The necessity of working on developing the process of identifying errors, addressing them, and the ability to take action can lead to base on the nature of employees' work and responsibility in the field of strategic planning for important projects and pathways supporting the national economy in the future.Research paper.